Laser-stimulated fluorescence refines flight modeling of the early cretaceous bird sapeornis. - Serrano Alarcón, Francisco José; Pittman, Michael; Kaye, Thomas G.; Wang, Xiaoli; Zheng, Xiaoting; Chiappe, Luis M. (American Museum of Natural History, 2020)
Unseen and difficult-to-see soft tissues of fossil birds revealed by laser-stimulated fluorescence (LSF) shed light on their functional morphology. Here we study a well-preserved specimen of the early pygostylian Sapeornis chaoyangensis under LSF and use the newly observed soft-tissue data to refine previous modeling of its aerial performance and to test its proposed thermal soaring capabilities. Under LSF, the body's lateral outline is observed, permitting direct estimates of the body's disc surface that generates drag during flight (Sb). This surface and the body drag coefficient-which is better estimated knowing Sb- are influential parameters in modeling flight dynamics. In particular, we focus on two aspects of flight dynamics: the calculation of the power margin during flapping flight (power curve), and the sinking speed during gliding (glide polar). Results from revised models using our direct soft-tissue measurements support the notion that Sapeornis was a thermal soarer that glided for long periods. LSF also confirms the absence of a true alula in Sapeornis. While the deployment of the alular digit could have enhanced control during slow flight, the position of this digit along the handwing (distal part of the wing) suggests limited maneuverability. This study demonstrates how soft-tissue preservation can be incorporated into modeling of flight dynamics in light of ever-improving palaeontological imaging techniques.
https://digitallibrary.amnh.org/collections/7f37d745-a9ae-46d0-9cb9-840b06458c19?cp.page=2
Keywords: Aves fósiles - Vuelo; Paleontología; Fluorescence; Soaring; Fossil soft-tissue; Flight reconstruction